Study on Strength Variation of Permeable Concrete Based on Differential Calorimetry Method and Multi-Index Test. (20th August 2019) - Yang, Sanqiang; Guo, Meng; Duan, Shichao; Liu, Na; Wu, Haonan; Du, Erxia; Liang, Meichen
Abstract : With the implementation of the Xiongan New Area and the urbanization construction plan surrounding the Beijing-Tianjin satellite, it is urgent to study and apply the sponge-permeable paving materials to solve the "urban waterlogging and heat island effect." In this paper, the hydration microscopic characteristics of cementitious materials are analyzed by means of the differential scanning calorimetry (DSC) test. The test of water-cement ratio, porosity, and gradation structure on the strength and permeability coefficient is emphasized, and the strength change rule of porous permeable concrete is obtained. The research results are shown as follows: (1) The DSC test shows that the effect of temperature on the hydration process of cement is obvious. With the increase of temperature, the two exothermic peaks of cement hydration increase significantly and tend to overlap and the exothermic process is shortened. At 85°C, only one exothermic peak appeared, indicating that C3S hydration and ettringite formation process were completed at the same time in a relatively short time. (2) The optimal water-binder ratio of pervious concrete ranges from 0.24 to 0.30, and the optimal porosity ranges should be controlled within the range of 15%–25%. Moreover, the open gradation of pervious concrete mix ratio design is selected, and the cement content should be within the range of 20%–25%. (3) The mathematical model of permeability coefficient and porosity ratio of permeable concrete is established:k = − 0.0003 n 2 + 0.0057 n − 0.0044 ; the mathematical model of permeability coefficient and compressive strength of open-graded pervious concrete:k = 0.99006 − 0.05389 c + 8.02 × 10 − 4 c 2 . The research results can provide theoretical support and technical guidance for the design and construction of permeable materials of sponge cities in Xiongan New Area and surrounding ring new area, which are of great engineering value.